CAPRIN E BRUCELLOSIS IN THREE DISTRICTS OF THE CAÑETE PROVINCE, LIMA - Toledo E., Marcel (2007)
The objective of the present epidemiological study was to determine the prevalence of brucellosis in raised goats under a barn-feeding system in the districts of San Vicente, Nuevo Imperial and San Luis, Cañete Province, Lima. Blood samples were collected from 385 goats of three or more months of age, not vaccinated against caprine brucellosis and belonging to 21 herds. Results showed four sero-positive goats to the Rose Bengal test and only one to the Complement Fixation test. The prevalence of caprine brucellosis was estimated at 0.26 ± 0.04%. This low prevalence could be due to the positive effect of the Control and Eradication Program of Caprine Brucellosis conducted by the Peruvian Ministry of Health and the National Service of Agrarian Health (SENASA) since the year 2000 in the province of Cañete.